ESTUDO DO COMPORTAMENTO DE RESINAS BULK FILL EM RESTAURAÇÕES CLASSE I POR MEIO DE MICROTOMOGRAFIA COMPUTADORIZADA E MICROTRAÇÃO - ALMEIDA JUNIOR, Lauber Jose dos Santos (2017)
The polymerization shrinkage (PS) and the detrimental effects have been the focus of studies with the aim of improving the performance of composite resins. The simplicity of technique due to the possibility of single fill in large quantities have allowed bulk fill composite resins (BFC) to be indicated to minimize this shrinkage. This thesis, divided in two chapters, aimed to evaluate the behavior of bulk fill composite resins in class I restorations by mans computerized microtomography (μCT) and microtensile bond strength (μTBS). Chapter I evaluated the PS and μTBS in BFC and conventional class I restorations composite resins, and the correlation between these factors. Class I cavities (4 x 5 x 4 mm), (factor-C = 4.2), were created in human third molars that were free of caries, which were randomized and divided into 4 groups (n = 6): Z350 XT(+): incremental insertion (II) and manual fill (MF); Z350 XT(-): single insertion (SI) and MF; TBF (Tetric N-Ceram Bulk Fill: SI and MF); and SFU [SonicFill: SI and ultrasonic fill (UF) ]. The teeth were scanned and analyzed in μCT at two times: T0- after the filling of the cavity with composite resins and T1- after the polymerization for PS. After 1 week, the teeth were sectioned crosswise in the buccolingual and mesiodistal directions to obtain specimens with approximately 1 mm² thickness and fixed to universal test machine device to perform μTBS. The data showed a statistically significant difference for PS between the groups Z350 XT(+) e Z350 XT(-), and between SF e Z350 XT(-) (Kruskal-Wallis and Dunn, p<0.05). he μTBS was higher for Z350 XT (+) than the other groups (p <0.05) and there was no correlation between PS and μTBS (p> 0.05). It was concluded that the BFC type present a PS similar to that of the conventional nanoparticulate composite resin inserted using the incremental technique. The bond strength was higher for the composite resin incrementally inserted, which presented a lower number of pre-test failures when compared to bulk fill composites. No correlation was observed between the PS and bond strength when bulk fill and conventional composites were used. Chapter II evaluated the volume of polymerization shrinkage (VS), gap (VG) and void (VV) using μCT in BFC and conventional class I restorations, and their correlations. Class I cavities (4 x 5 x 4 mm), factor-C = 4.2, were created in human third molars that were free of caries, which were randomized and divided into 5 groups (n = 6): Z350 XT(+) (II/MF); Z350 XT(-) (SI/MF); TBF (SI/MF); SFM [ (SonicFill: SI and MF) ] and SFU (SI/UF). The teeth were scanned and analyzed in μCT at two times: T0- after the filling of the cavity with composite resins and T1- after the polymerization for VG and VV, and for VS (T1-T0). After 1 week, the teeth were sectioned crosswise in the buccolingual and mesiodistal directions to obtain specimens with approximately 1 mm² thickness and fixed in a universal testing machine to perform μTBS. Kruskal-Wallis and Dunn tests showed statistically significant difference in VS for groups Z350 XT(+) and Z350 XT (-), and between SFU and Z350 XT(-), and difference between VV for Z350 XT(+) and BFC (p <0.05). There was no difference in VG between the conventional and BFC (p>0.05). There is a positive correlation between VS versus VG and between VS versus VV (Spearman, p <0.05). It was concluded that BFCs of both sonic and manual insertion showed polymerization shrinkage and gap formation similar to the incrementally inserted nanoparticulate conventional resin. There is a positive correlation between polymerization shrinkage and final gap formation, as well as between polymerization shrinkage and void in composite resins. The final gap was formed mainly by the initial gap generated during the insertion/filling of the composite in the cavity and not to the polymerization shrinkage.